Combining node-centered parallel radiation transport and higher-order multi-material cell-centered hydrodynamics methods in three-temperature radiation hydrodynamics code TRHD - Sijoy, C.D.; Chaturvedi, S. (Computer physics communications, 2016)
Higher-order cell-centered multi-material hydrodynamics (HD) and parallel node-centered radiation transport (RT) schemes are combined self-consistently in three-temperature (3T) radiation hydrodynamics (RHD) code TRHD (Sijoy and Chaturvedi, 2015) developed for the simulation of intense thermal radiation or high-power laser driven RHD. For RT, a node-centered gray model implemented in a popular RHD code MULTI2D (Ramis et al., 2009) is used. This scheme, in principle, can handle RT in both optically thick and thin materials. The RT module has been parallelized using message passing interface (MPI) for parallel computation. Presently, for multi-material HD, we have used a simple and robust closure model in which common strain rates to all materials in a mixed cell is assumed. The closure model has been further generalized to allow different temperatures for the electrons and ions. In addition to this, electron and radiation temperatures are assumed to be in non-equilibrium. Therefore, the thermal relaxation between the electrons and ions and the coupling between the radiation and matter energies are required to be computed self-consistently. This has been achieved by using a node-centered symmetric-semi-implicit (SSI) integration scheme. The electron thermal conduction is calculated using a cell-centered, monotonic, non-linear finite volume scheme (NLFV) suitable for unstructured meshes. In this paper, we have described the details of the 2D, 3T, non-equilibrium, multi-material RHD code developed with a special attention to the coupling of various cell-centered and node-centered formulations along with a suite of validation test problems to demonstrate the accuracy and performance of the algorithms. We also report the parallel performance of RT module. Finally, in order to demonstrate the full capability of the code implementation, we have presented the simulation of laser driven shock propagation in a layered thin foil. The simulation results are found to be in good agreement with the known solutions of RHD problems.